PENGARUH JACKETING PADA KELAYAKAN OPERASIONIL PROSES COLUMN DISTILASI = THE INFLUENCE OF JACKETING ON PROFICIENCY OF DESTILATION COULUMN PROCES - M. N. Setia Nusa (Majalah Ilmiah Pengkajian Industri, 2016)
AbstractÂ A column distillation has been operated for 42 years , Leaking often happens in top of tray part. it has been repaired by jacketing and patching. Meantime there are still some leaks and damages happens in top tray. Some research and repair action were conducted to avoid the same problem in the future and to know the recent condition of the column using fractography examination, Metallography examination, hardness test, chemical composition analysis, thickness and pundit and the result will be deriving us to the caused of the failure and to the impact of the used of patching and jacketing on material. The research results reveal any corrosion and the elements that have been uneven jacketing conditions only at the top of the destilation column.Â AbstrakColumn distilasi telah beroperasi selama 42 tahun, beberapa kali mengalami kebocoran di dinding tray bagian atas dan setiap kali repair dilakukan dengan jacketing dan patching. Pada saat ini masih ditemukan ada beberapa kerusakan/kebocoran juga pada tray atas, untuk itu perlu dilakukan penelitian untuk tindakan repair dan mengetahui kondisi terkini column melalui pemeriksaan fraktografi, metalografi, uji kekerasan, komposisi kimia, ketebalan dan pundit sehingga secara keseluruhan hasilnya dapat mengetahui penyebab kerusakan dan mengetahui pengaruh patching dan jacketing pada material. Hasil penelitian ditemukan adanya unsur korosi serta kondisi jacketing yang sudah merata pada bagian atas coulumn destilasi.Â